Marka adı stratejisi ve Türk işletmelerinin yabancı sözcük içeren marka adı belirlemelerine ilişkin bir araştırma - Tığlı, Mehmet; Cesur, Zafer (İktisadi ve İdari Bilimler Dergisi, 2006)
Branding strategies include defining brand name for a product. Before launching a product to market, a simple, original, accurate brand name must be determined by the marketing professionals. Products have Turkish brand names which are produced by Turkish firms can be more valuable and acceptable than products which h ave brand names in other languages for Turkish consumers. Brand names which have foreign words may be risky for its success. In this article, this lan guage problem will be described theoretically. Later, there will be a market research measuring the attitudes of consumers on the brand name practices in Turkish or foreign language.
Keywords: Marka, Marka Adı, Markalama, Marka Adı Stratejileri